MENELAAH PERSPEKTIF PENGGUNA LAYANAN DAN SEJAWAT PROFESI TENTANG PROFIL PRIBADI KONSELOR EFEKTIF - Edris Zamroni; Gudnanto Gudnanto; Susilo Rahardjo (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This study is motivated by the assumption that the personal qualities of counselors are essential to be studied because the effectiveness of counseling services is also influenced by the subjective views of clients towards counselors as professionals who are asked to help them. In addition, there are different views on the personal profile of an effective counselor from the side of service users, which include principals, subject teachers, administrative staff, students, and parents, as well as the guidance and counseling professional community regarding how the counselor's figure is considered effective to provide counseling services to them. This study aims to determine the views and expectations of service users and professional colleagues regarding the personal profile of effective counselors. The method used was descriptive quantitative research. The results showed that effective counselors must display good personal identity through integrity, emotional stability, and psychological maturity in providing guidance and counseling services. This has implications for the performance of counselors in serving clients who must demonstrate self-management and integrity to gain more trust in the community.